Crystal-Chemical and Structural Characterization of Omphacite in High-Pressure Eclogites From the Arquía Complex on Southwestern Pijao, Central Cordillera (Colombian Andes) - Castellanos-Alarcón, Oscar Mauricio; Cedeño Villarreal, Karoll Michelle; Toro Hernández, Robert Antonio; Ríos-Reyes, Carlos Alberto; Henao-Martínez, José Antonio; Zuluaga-Castrillón, Carlos Augusto (Frontiers in Earth Science, 2022)
Omphacite found in eclogites from the Arquía Complex (Colombia) was characterized using scanning electron microscopy, electron probe microanalysis and single-crystal X-ray diffraction. The sample is chemically homogeneous. Omphacite usually shows symplectitic intergrowths or a relictic character partially and totally included in amphibole. The transformation of omphacite to symplectites colonies characterizes the initiation of the eclogites retrograde metamorphism. The reaction history can be summarized as the decomposition of omphacite into symplectites as a product of decompression through the reaction: omphacite + quartz = plagioclase + clinopyroxene (low in Na), which can be considered as a discontinuous precipitation reaction. The structure of the studied omphacite single-crystal is successfully refined in the P2/c space group. This structure is interpreted as an intermediate towards omphacite with space group P2/n. The structure of omphacite shows silicate chains formed by two crystallographically different silicon tetrahedra (T1 and T2) with an O2-O3-O2 angle of 169.002 (2)°, indicating that the chain is slightly distorted. The Na and Ca cations occupy the octahedral and 8-coordination sites. Fe occurs as Fe2+ and Fe3+ and are distributed over the octahedral sites M1 and M11, respectively.